Experimental investigation on thermal-hydraulic characteristics of endothermic hydrocarbon fuel in 1 mm and 2 mm diameter mini-channels. (25th July 2017) - Guo, Yong; Bi, Qincheng; Liu, Zhaohui; Yang, Zhuqiang; Jiang, Lei
Highlights: We found thermal-hydraulic characteristic of endothermic fuel was a quintic curve. Boiling and pyrolysis caused the transition of the pressure drop profile. Transition point of the curve related to fuel temperature regardless of heat flux. Multi-valued characteristic also existed at supercritical pressure conditions. Bigger magnitude of pressure drop variation in bigger diameter channel. Abstract: The thermal-hydraulic characteristics of endothermic hydrocarbon fuel were experimentally investigated in circular mini-channels with inner diameters of 1.0 and 2.0 mm and heated length of 800.0 mm. The effects of heat flux ranging from (400 to 1750) kW·m −2, pressure from (1.0 to 6.0) MPa, and inner diameter were studied. We found that the thermal-hydraulic characteristics of endothermic fuel could be described by a quintic curve. Two positive slope regions and two negative slope regions were experimentally obtained. The boiling or pseudo-boiling, and fuel pyrolysis which led to the rapid density reduction caused two negative slope regions in the curve. The negative slope region at fuel pyrolysis conditions always existed at the tested subcritical and supercritical pressures. The effect of heat flux on the thermal-hydraulic characteristics was not significant. The transition points were fixed and connected to the zeotropic process or pseudo-boiling temperature and pyrolysis reactions regardless of heat fluxes. The multi-valued characteristics can be reduced in small channels, as the magnitude of pressure drop variation was much larger in big channels. The study on thermal-hydraulic characteristics of endothermic fuel starts a new direction in fluid dynamics considering the chemical reaction.